A 7-year-old girl with multiple skin ulcers: Case report and literature review. Issue 4 (December 2015) - Sobh, Eman; Bahour, Amira; Elsayed, Sahar; Amer, Wegdan
Abstract: Introduction: There has been an increase in the number of tuberculosis (TB) cases worldwide, but TB of the skin remains rare. Case presentation: A case of 7-year-old girl with multiple ulcerating nodules who presented with four ulcers in the skin of the left elbow. The patient was unresponsive to broad-spectrum antibiotics treatment initially. Because of poor clinical response to conventional therapy, TB was suspected. Although tuberculin skin test was negative, positive QuantiFERON TB Gold test and clinical picture strongly indicated TB. Clinical diagnosis was confirmed by positive culture for Mycobacterium tuberculosis . Conclusion: A high index of clinical suspicion is necessary to suspect TB of the skin. Positive culture remains the gold standard for diagnosis.